Macro econometric modelling: A practical approach under EViews, with a focus on Africa - Brillet, Jean Louis (International Food Policy Research Institute, 2015)
Many books have been written on the subject of macroeconometric modelling that the usefulness of adding a new general contribution can be questioned. Our approach will be original in two ways. First, it will be extremely developed, with the goal of giving modelers a complete set of elements which will allow them to build their own models. To this end, our presentation is complemented by examples using the EViews software, from general strategies to technical details. The associated programs and files will be provided. Second, it will focus on Africa, to which all our examples will relate. We will also present the specific issues, problems and strategies for modeling this region and developing countries in general.